Ultrasonography of the prostate gland and testes in dogs - Barbosa de Souza, Mírley; Silva, Lúcia Daniel Machado da; Moxon, Rachel; Russo, Marco; England, Gary C.W. (BMJ Publishing Group, 2017)
Ultrasonographic imaging is an important diagnostic tool because it allows assessment of the shape, size, position, margination and internal architecture of organs, as well as facilitating the study of vascular supply and vascularisation. Recently, there has been considerable development of B-mode, Doppler and contrast-enhanced ultrasonography for examination of the reproductive tract of dogs, both for studying normal physiology and in the clinical setting. This article describes the practical examination of the canine prostate gland and testes using a variety of ultrasound techniques, and details the normal appearance and blood flow of these organs as well as changes that may be observed with common reproductive disorders.